Re-exposure animal bite management among incident animal bite cases in a secondary care Hospital in Delhi, India - Saurav Basu; Warisha Mariam; Sahadev Santra; Suneela Garg; Rajiv Singhal (Wolters Kluwer Medknow Publications, 2020)
Complete postexposure prophylaxis with 4 doses of anti-rabies vaccine (ARV) in a previously vaccinated (nonnaïve) individual results in administration of two extra ARV doses resulting in wastages of precious resources comprising vaccine logistics, human resources, physician, and patient time. This cross-sectional study conducted in a secondary care hospital in Delhi among 175 incident animal bite cases observed 39 (22.3%) had an animal-bite history within the previous 5 years. A total of 19 (10.8%) cases reported a history of complete ARV vaccination during a previous animal-bite exposure. However, in the absence of supportive patient medical documentation, all the animal bite cases without exception were prescribed a full course of ARV irrespective of their previous exposure status. Rabies immunoglobulins (anti rabies serum) were also re-administered in 13 (81.2%) cases. National guidelines for rabies prophylaxis should, therefore, consider the inclusion of an explicit decision-making algorithmic mechanism when the health-care provider is confronted with this situation carrying the potential for hidden vaccine wastage.